Brief report: Attention patterns to non-social stimuli and associations with sensory features in autistic children. (October 2022) - Chen, Yun-Ju; Harrop, Clare; Sabatos-DeVito, Maura; Bulluck, John; Belger, Aysenil; Baranek, Grace T.
Abstract: Background: Aberrant attention patterns have been commonly reported in autistic children. However, few studies have examined attention to non-social stimuli varying in salience and complexity using eye-tracking technology, as well as their links to clinical sensory features. Method: Forty-one children [16 with autism spectrum disorder (ASD), 10 with developmental delay (DD), and 15 neurotypical (NT)] ages 4 to 13 years were included in this cross-sectional study. Children completed a passive-viewing eye-tracking task designed to measure visual attention (e.g., fixation duration and count) to non-social stimuli with sensory qualities involving motion (spinning or non-spinning) and sound. Parents completed a clinical questionnaire about their child's sensory behaviors. Eye-tracking metrics were compared across stimulus conditions and diagnostic groups, and their associations with parent-report sensory features were examined. Results: Overall children showed longer fixation durations and fewer fixation counts to more complex stimuli (e.g., moving or spinning objects), but such facilitatory effects of stimulus properties tended to be less evident in DD versus ASD or NT groups. More clinical sensory features, especially hyperresponsiveness, were moderately to highly associated with quicker initial fixations and longer fixation durations across stimulus conditions in ASD, but not in DD and NT groups. Conclusion: The overall attention and initial orientation to non-social stimuli were comparable across autistic children and their non-autistic peers, with some sensory properties such as dynamic motion producing a facilitatory effect (i.e., fewer fixations of longer durations) on attention. However, sensory differences, particularly hyperresponsiveness, might underlie attention patterns as impacted by stimulus properties specifically in autism. Highlights: This study examined attention to non-social stimuli that varied in salience and complexity using eye-tracking. Children generally looked at moving or spinning objects with fewer fixations of longer duration (i.e., faciliatory effect). The facilitatory effect of stimulus properties was overall less evident in DD compared to ASD and NT groups. Visual attention and sensory features were found to have a unique connection in ASD, but not in DD and NT groups.